ANALISA PENGAMANAN DALAM LEMBAGA PEMASYARAKATAN KELAS I CIPINANG BERDASARKAN UNDANG - UNDANG NOMOR 22 TAHUN 2022 TENTANG PEMASYARAKATAN - Paslah Dwi Anggara, Rio; Gultom, Potler (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2024)
Security conditions in correctional institusion are the main reference for the implementation of various activities in correctional institutions. In Article 1 Paragraph 13 of Law No. 22 of 2022, it is stated that Security is all forms of activities in order to prevent, enforce, and recover security and order disturbances that are held to create safe and orderly conditions in state prisons and correctional institutions. In this study, the author will discuss the Implementation of Security in the Cipinang Class 1 Correctional Institution based on Law Number 22 of 2022 and the obstacles encountered in the Implementation of Security in the Cipinang Class 1 Correctional Institution. The legal research method used is the normative juridical legal method. The Cipinang Class I Correctional Institution is considered to meet the characteristics of Security regulated in Article 82 paragraph 2 of Law No. 22 of 2022 as it already has a security system with capabilities equipped with finger and face recognition, and there are CCTV and other detection tools to tighten security and obstacles in the implementation of security and order in the Cipinang Class I Correctional Institution such as the number of inmates who are over capacity, the quality of human resources and infrastructure facilities that are still lacking, and so on. It is recommended that prison officers must fully carry out their duties and responsibilities, so that security and order disturbances in the form of crimes and violations committed by insiders and outsiders are minimal. And supported by the Head of the Regional Office and the Head of the Pas Division for facilities and infrastructure.